If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b = 4b Solving b = 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. b + -4b = 4b + -4b Combine like terms: b + -4b = -3b -3b = 4b + -4b Combine like terms: 4b + -4b = 0 -3b = 0 Divide each side by '-3'. b = 0 Simplifying b = 0
| 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 | | x-8.2=4.5 | | 9r-6r+6=6r+6-r | | -2w-4w-24=48 | | 736=4(x+18) | | 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 | | 5(-x)-5= | | 0.6x-1=0.5 | | -296=-8(-8x-3) | | (x+8)(2x+4)(3x-6)=0 |